FRI0544 Administration of Routine Preventative Vaccinations in Children with Polyarticular Juvenile Idiopathic Arthritis Receiving Adalimumab. (10th June 2014) - Minden, K.; Karunaratne, M.; Kupper, H.; Kalabic, J.
Abstract : Background: Adalimumab (ADA) has been shown to be safe and effective in polyarticular juvenile idiopathic arthritis (pJIA), and is approved for use in moderate to severe pJIA patients (pts) ≥4 years (yrs) in the US, Australia, and Japan, and in the EU for pts ≥2 yrs. Objectives: Pts with pJIA are candidates for routine childhood vaccinations, according to the respective national guidelines. This post hoc report describes the observed use of vaccines in pJIA pts receiving ADA in 3 clinical trials and one registry. Methods: Pts with active pJIA were enrolled in one of the following trials: M10-444 (ages 2 to <4 or ≥4 weighing <15 kg in US, EU), M10-240 (ages 4-17 in Japan), DE038 (ages 4-17 in US, EU) or the STRIVE (P10-262) registry (ages 4-17 in US, EU, and Australia). Pts in these studies received ADA +/- methotrexate. Vaccinations were administered based on the judgment of the study investigator or the treating physician. Descriptive statistics were used to summarize all vaccinations, including the influenza vaccine. Adverse events (AEs) related to active influenza virus infection events occurring within 270 days after influenza vaccination were collected by a predefined MedDRA query 15.1 [Lack of efficacy/effect Influenza (Vaccination Product Specific)]. Results: A summary of all vaccinations is presented in the Table. Among the different types of vaccines, the influenza vaccine was the most frequently administered: 55, 63, 10 and 22 influenza vaccines were administered in DE038, M10-240, M10-444 and P10-262, respectively. In addition, pneumococcal, human papilloma virus, diphtheria, tetanus and/or pertussis, hepatitis A and B, and polio vaccines were administered. 2 pts each received >5 vaccinations in DE038 and M10-240, while 3 pts each in M10-444 and P10-262 received >1 but <5 vaccinations. The influenza vaccine was administered to 32/171 (19%), 20/25 (80%), 6/32 (19%) and 21/533 (4%) of pts during the course of the study in DE038, M10-240, M10-444 and P10-262 respectively, and the mean (SD) time to 1st influenza vaccination was high: 675 (618), 189 (80), 93 (90) and 443 (396) days. The rates of influenza-related AEs reported for pts who received influenza vaccinations and those who did not were: 13% vs 9% for DE038, 15% vs 20% for M10-240, 0% vs 12% for M10-444, and 5% vs 0.4% for P10-262. Conclusions: These data support the idea that pJIA pts treated with ADA can be immunized with routine, inactive, preventative vaccines, such as the influenza vaccine. However, not all of the eligible pts were vaccinated on time according to the Centers of Disease Control (CDC) recommendations, and many pts were not vaccinated at all suggesting that physicians may be reluctant to use vaccines in children receiving antirheumatic therapies. Further investigation regarding rheumatologists' vaccination practices for pts with JIA is warranted. Acknowledgements: AbbVie sponsored the studies (NCT00774537, NCT00690573, NCT00048542 and NCT00783510 ), contributed to the study design, and participated in collection, analysis, and interpretation of data, and in writing, reviewing, and approval of the final version. Medical writing support was provided by Jessica L. Suboticki, PhD, and Naina Barretto, PhD, of AbbVie. Disclosure of Interest: K. Minden Grant/research support: Pfizer, AbbVie, Inc., Consultant for: Pfizer, AbbVie, Roche/Chugai, Novartis, Medac and Pharm-Allergan, Speakers bureau: Pfizer, abbVie, Roche/Chugai, Novartis, Medac and Pharm-Allergan, M. Karunaratne Shareholder of: AbbVie, Inc., Employee of: AbbVie, Inc., H. Kupper Shareholder of: AbbVie, Inc., Employee of: AbbVie, Inc., J. Kalabic Shareholder of: AbbVie, Inc., Employee of: AbbVie, Inc. DOI: 10.1136/annrheumdis-2014-eular.1559